1984
DOI: 10.1128/jcm.20.3.575-576.1984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rapid latex agglutination test for identification of group D streptococci

Abstract: The SeroSTAT latex agglutination test (Scott Laboratories, Inc., Fiskesville, R.I.) for identification of group D streptococci was compared with bile-esculin agar and Lancefield grouping by using 110 clinical isolates of group D streptococci (S. faecalis, 74; S. bovis, 24; S. durans, 3; S. faecium, 9) and 65 viridans streptococci (S. anginosus-constellatus, 2; Streptococcus MG, 15; S. sanguis II, 14; S. mitis, 7; S. mutans, 5; S. salivarius, 8; S. sanguis I, 8; S. acidominimus, 1; S. morbillorum, 2; S. pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although all the Lancefield reagents have been used on nonbeta-hemolytic streptococci, only group B and D reagents are recommended for this purpose (5). Major problems, such as false-negative results with group D reagents (3,6,18,21) and cross-reactions between Streptococcus pneumoniae (23) and Klebsiella pneumoniae with the group C reagent, have still been encountered in these evaluations (16). Recently, Birch et al (2) reported that 17 of 36 strains of S. faecalis isolated from patients in four hospitals in England possessed Lancefield antigen reactive with both group D and group G reagents.…”
mentioning
confidence: 99%
“…Although all the Lancefield reagents have been used on nonbeta-hemolytic streptococci, only group B and D reagents are recommended for this purpose (5). Major problems, such as false-negative results with group D reagents (3,6,18,21) and cross-reactions between Streptococcus pneumoniae (23) and Klebsiella pneumoniae with the group C reagent, have still been encountered in these evaluations (16). Recently, Birch et al (2) reported that 17 of 36 strains of S. faecalis isolated from patients in four hospitals in England possessed Lancefield antigen reactive with both group D and group G reagents.…”
mentioning
confidence: 99%